Marketing Strategies of Commercial and Co-Operative Banks and Role of Banking In Haryana: An analysis of marketing strategies and customer acceptance in the banking sector of Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In present study we have triedto  assess the new products and servicesavailable from the banks to the customers in Haryana, to ascertain the impactof information technology on the bank deals in Haryana, to ascertain themarketing strategies adopted by the bank branches in Haryana for marketingtheir products and services, to examine the extent of acceptance of the bankingproducts and services by the customers in Haryana, and to evaluate the attitudeof the bank personnel vis-a-vis. customers towards marketing of new productsand services of banks.